Expanded Use of Vorasidenib in Non-Enhancing Recurrent CNS WHO Grade 3 Oligodendroglioma - Alexander S. Himstead; Jefferson W. Chen; Eleanor Chu; Mari A. Perez-Rosendahl; Michelle Zheng; Sherin Mathew; Carlen A. Yuen (Biomedicines)
Background/Objectives: Anaplastic oligodendrogliomas (AOs) are central nervous system (CNS) World Health Organization (WHO) grade 3 gliomas characterized by isocitrate dehydrogenase (IDH) mutation (m)IDH and 1p/19q codeletion. AOs are typically treated with surgery and chemoradiation. However, chemoradiation can cause detrimental late neurocognitive morbidities and an accelerated disease course. The recently regulatory-approved vorasidenib, a brain-penetrating oral inhibitor of IDH1/2, has altered the treatment paradigm for recurrent/residual non-enhancing surgically resected CNS WHO grade 2 mIDH gliomas. Though vorasidenib can delay the time to chemoradiation for grade 2 gliomas, the implications for vorasidenib in non-grade 2 mIDH gliomas are not well understood. Results: We present a case of a 71-year-old male with a grade 3 non-enhancing oligodendroglioma successfully treated with vorasidenib with an 11% reduction in residual tumor volume. Vorasidenib was well tolerated in our patient with a mild elevation in his liver transaminases that resolved following a brief interruption in treatment. Conclusions: Our case suggests that vorasidenib may impart therapeutic benefits in this setting. This case illustrates the need for further investigation into these less commonly addressed scenarios and treatment strategies that extend beyond current guidelines.